2023
DOI: 10.3389/fpsyg.2023.1165830
|View full text |Cite
|
Sign up to set email alerts
|

Family intimacy and adolescent peer relationships: investigating the mediating role of psychological capital and the moderating role of self-identity

Abstract: According to existing research, family intimacy affects the formation of peer relationships among adolescents; Parent–child relationships may influence children’s relationships with peers, but the mechanism of its influence is still unclear due to the uncertainty of its effect. According to the ecological systems theory, this study examines how family intimacy affects adolescent peer relationships through psychological capital and how self-identity moderates this effect. These hypotheses were tested based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 114 publications
(128 reference statements)
0
0
0
Order By: Relevance
“…The findings suggest that parents’ educational level and occupational status have stronger associations with components of SSWB, particularly student cooperation, than other FSES indicators, thereby establishing a connection between FSES and SSWB. As previous youth development research has indicated, adolescence is a crucial developmental period where peer relationships become a priority ( Zhou et al, 2023 ). Peer relationships become more prominent during adolescence as they place greater importance on the expectations and acceptance of their peers ( Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that parents’ educational level and occupational status have stronger associations with components of SSWB, particularly student cooperation, than other FSES indicators, thereby establishing a connection between FSES and SSWB. As previous youth development research has indicated, adolescence is a crucial developmental period where peer relationships become a priority ( Zhou et al, 2023 ). Peer relationships become more prominent during adolescence as they place greater importance on the expectations and acceptance of their peers ( Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%